Cortical vision, MRI and developmental outcome in preterm infants. Issue 4 (11th March 2008) - Atkinson, J; Braddick, O; Anker, S; Nardini, M; Birtles, D; Rutherford, M A; Mercuri, E; Dyet, L E; Edwards, A D; Cowan, F M
Abstract : Objectives: To test two measures of visual cortical function in the first year of life as early markers of functionally significant brain damage in infants born preterm: orientation-reversal visual event-related potentials (OR-VERP) and a behavioural test of cortically controlled visual attention-fixation shifts under competition (FS). Also to examine how these measures relate to (1) perinatal brain insults identified by MRI, and (2) later neurodevelopmental status. Patients and methods: After neonatal and term-age-equivalent MRI, 26 preterm infants (<32 weeks of gestational age, mean 28.1 weeks) were given the OR-VERP and FS tests before 12 months post-term age and a neurodevelopmental assessment (Griffiths Scales) at 2 years. MRI scans examined for parenchymal lesions, intraventricular haemorrhage, ventricular dilatation and diffuse excessive high signal intensity were classified into three categories of severity. Cortical visual test results were compared across these categories and examined as predictors of developmental status at 2 years. Results: 26 infants were studied. 13/25 infants showed significant OR-VERP responses. 12/26 showed normal FS performance. On both tests, the proportion of infants meeting these criteria decreased significantly with MRI severity. As predictors of Griffiths developmental quotient ⩽80, the FS test had a sensitivity of 100%, a specificity of 61%, and positive and negative predictive values of 50% and 100%, respectively; corresponding values for OR-VERP were 86%, 65%, 50% and 92% . Conclusions: Visual cortical tests can provide early indicators of the functional impact of perinatal brain damage in the preterm infant.